An Ultraviolet–Visible and Near‐Infrared‐Responded Broadband NIR Phosphor and Its NIR Spectroscopy Application - Zhou, Xufeng; Geng, Wanying; Li, Junyi; Wang, Yichao; Ding, Jianyan; Wang, Yuhua (Advanced optical materials, 2020)
High‐radiance near‐infrared (NIR) phosphor‐converted light‐emitting diodes (pc‐LEDs) are demanded for wearable biosensing devices and the properties of these pc‐LEDs are highly dependent on the performance of the NIR phosphor. An ultraviolet–visible and NIR‐responded broadband NIR NaScGe2O6:Cr3+ phosphor is reported. Under 490 nm excitation, NaScGe2O6:Cr3+ shows broad emission band from 700 to 1250 nm, which covers the first and second NIR windows. An NIR pc‐LED with radiant flux of 12.07 mW@350 mA is realized based on NaScGe2O6:Cr3+ and 450 nm blue LED chip. The ability of high‐power NIR light of the NIR pc‐LED to penetrate human tissues is observed successfully. Additionally, in NaScGe2O6:Cr3+, the luminescence performance of Cr3+ under 808 nm laser excitation is achieved for the first time. A broadband near‐infrared (NIR) emission phosphor NaScGe2O6:Cr3+ with super‐wide response range is developed. The high‐power NIR phosphor‐converted light‐emitting diode is prepared and the ability of the high‐power NIR light to penetrate human tissues is observed successfully. In addition, the luminescence performance of Cr3+ under 808 nm laser excitation is achieved for the first time in NaScGe2O6:Cr3+.